Influence of blue and violet LED and infrared laser on the temperature of bleaching protocols in different concentrations of hydrogen peroxide - Elma Vieira Takeuchi; Joatan Lucas de Sousa Gomes Costa; Carmem Lúcia de Arroxelas Silva; Antonia Patricia Oliveira Barros; Barbara Leite Machado; Heitor Hussni Casarin; João Felipe Besegato; Milton Carlos Kuga; Cecy Martins Silva (Photodiagnosis and Photodynamic Therapy)
Background: The photo-acceleration of bleaching gels by lights has been extensively researched. However, the induced temperature increase during this process needs to be further evaluated to prevent damage to the dental pulp. Therefore, the objective of this study was to evaluate the surface and intrapulpal temperature kinetics of different concentrations of hydrogen peroxide (HP) gels photo-accelerated by blue or violet light and infrared laser. Methods: The whitening gels at concentrations of HP35, HP15, and HP6 % were irradiated with blue and violet LED/laser on the surface of a human canine tooth. The surface temperature variation (∆Ts) was evaluated using a pH meter, while the intrapulpal temperature variation (∆Ti) was assessed using a digital thermometer at intervals of 1, 15, and 30 min. Statistical analysis was conducted using a Two-way repeated measures ANOVA test, and Bonferroni post-test was applied at a significance level of 5 %. Results: All violet LED photo-accelerated groups showed a higher increase in ∆Ts compared to the blue LED/laser groups. However, there were no significant differences between the groups for ∆Ti. Conclusion: Although the photo-acceleration of HP35 and HP15 % gels with violet LED/laser has a greater increase in surface temperature compared to HP6 % gel, the different light systems do not significantly increase the intrapulpal temperature.